Implementation of Mycoplasma genitalium Diagnostics with Macrolide-Resistance Detection Improves Patient Treatment Outcomes in Bulgaria - Ivva Philipova; Maria Mademova; Elena Birindjieva; Venelina Milanova; Viktoriya Levterova (Diagnostics, 2024)
Background/Objectives: The increasing prevalence of Mycoplasma genitalium infections with macrolide-resistance, causing high azithromycin failure rates, is a major concern internationally. In response to this challenge, diagnostics that simultaneously detect M. genitalium and genetic markers for macrolide-resistance enable the therapy to be individually tailored, i.e., to implement resistance-guided therapy (RGT). This study aimed to evaluate patient treatment outcomes of M. genitalium therapy, guided by a macrolide-resistance assay in Bulgaria. Methods: Consecutively referred M. genitalium infection cases (n = 17) were analyzed for macrolide-resistance mutations (MRMs) and specific antimicrobial treatment was recommended accordingly (MRMs-negative infections received azithromycin and MRMs-positive infections received moxifloxacin). The treatment outcome based on test-of-cure was recorded, and the treatment failure rates and time to achieve a microbiological cure were compared to treatment outcomes in patients treated before the implementation of RGT. Results: Among patients given RGT (n = 17), the overall treatment failure rate was 1/17 (5.9%). This was significantly lower than the rate (47.6%) observed in patients treated pre-RGT (p = 0.002). The time to achieve a microbiological cure was 29.4 days (CI 24.5–34.3), compared to 45.2 days (CI 36.5–53.7) pre-RGT (p = 0.001). Conclusions: The implementation of M. genitalium diagnostics with macrolide-resistance detection improved treatment outcomes in Bulgaria, with significantly lower treatment failure rates and reduced time to achieve a microbiological cure. In light of the limited treatment options and concerns about their decreasing efficacy in response to misuse and overuse, a diagnostic macrolide-resistance assay is critical to direct the appropriate first-line treatment, to maintain the efficacy of antimicrobial treatment (antibiotic stewardship) and to minimize the spread of antimicrobial resistance.